Gender, Power, and Emotion: A Feminist Stylistic Analysis of Beyoncé’s 'If I Were a Boy - Situmorang, Nia Felicia; Sibarani, Lydia permata Sari; Simbolon, Febrian Valentino; Kerwin, Kerwin; Rangkuti, Rahmadsyah (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
This study applies Sara Mills’ feminist stylistics to Beyoncé’s If I Were a Boy to examine how linguistic structures reveal gender inequality in romantic relationships. The analysis at lexical, syntactic, and discourse levels shows how the song constructs and critiques dominant gender roles. Through hypothetical language and role reversal, the female narrator exposes emotional double standards and critiques male privilege. Key findings highlight how male autonomy and emotional detachment are normalized, while women are burdened with empathy and accountability. This study contributes to gender studies and media analysis by demonstrating how feminist stylistics can uncover embedded power imbalances in mainstream music.